Hemagglutinin virus-like particles incorporated with membrane-bound cytokine adjuvants provide protection against homologous and heterologous influenza virus challenge in aged mice - Bo Ryoung Park; Ramireddy Bommireddy; David Hyunjung Chung; Ki-Hye Kim; Jeeva Subbiah; Yu-Jin Jung; Noopur Bhatnagar; Christopher D. Pack; Sampath Ramachandiran; Shaker J.C. Reddy; Periasamy Selvaraj; Sang-Moo Kang (Immunity & Ageing, 2023)
Abstract Background Current influenza vaccines deliver satisfactory results in young people but are less effective in the elderly. Development of vaccines for an ever-increasing aging population has been an arduous challenge due to immunosenescence that impairs the immune response in the aged, both quantitatively and qualitatively. Results To potentially enhance vaccine efficacy in the elderly, we investigated the immunogenicity and cross-protection of influenza hemagglutinin virus-like particles (HA-VLP) incorporated with glycosylphosphatidylinositol (GPI)-anchored cytokine-adjuvants (GPI-GM-CSF and GPI-IL-12) via protein transfer in aged mice. Lung viral replication against homologous and heterologous influenza viruses was significantly reduced in aged mice after vaccination with cytokine incorporated VLPs (HA-VLP-Cyt) in comparison to HA-VLP alone. Enhanced IFN-γ+CD4+ and IFN-γ+CD8+ T cell responses were also observed in aged mice immunized with HA-VLP-Cyt when compared to HA-VLP alone. Conclusions Cytokine-adjuvanted influenza HA-VLP vaccine induced enhanced protective response against homologous influenza A virus infection in aged mice. Influenza HA-VLP vaccine with GPI-cytokines also induced enhanced T cell responses correlating with better protection against heterologous infection in the absence of neutralizing antibodies. The results suggest that a vaccination strategy using cytokine-adjuvanted influenza HA-VLPs could be used to enhance protection against influenza A virus in the elderly.